REGULARITIES OF ISOVALENT ATOM SUBSTITUTION INFLUENCE ON THE STRUCTURE OF AIILn BIIIO TYPE COMPOUNDS - Titov, Y.A.; Slobodyanik, M.S.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
Based on the analysis of the structural data of phases ((AII, AII*)(Ln, Ln*)2 B2 IIIO7 (AII = Ba, Sr, AII* = Sr, Ca, Ln = La, Nd, Ln* = Sm, Dy, BIII = In, Sc), the regularities of the influence of isovalent substitutions of AII and Ln atoms in the slab perovskite-like structure of AIILn2B2 IIIO7-type compounds on its structure were determined. It was obserbed that an increase in the degree of substitution of AII and Ln atoms in the slab structure of AII1−x, AxII*Ln2 B2IIIO7 and AIILn2−x Lnx*B2 IIIO7 type phases leads to an increase in the degree of deformation (Δ) of interblock polyhedra of AO9 and to a decrease in the length of the interblock distance A — O. It was found that the values of ΔAO9 and ΔAO12 in the structure of AII1−x, AxII*Ln2 B2 IIIO7 and AIILn2−x Lnx*B2IIIO7 depend on the type of syngonia of lattice and are highest in tetragonal solid solutions. The distribution of Ba, Sr, and REE atoms in (AII, AII*)(Ln, Ln*)2 B2IIIO7 structures is determined by the value of difference in their radii, with an increase contributing to the ordering of the distribution of Ba, Sr, and REE atoms in AO9 and AO12 polyhedra. Structural factors affecting the stability of (AII, AII*)(Ln, Ln*)2 B2IIIO7 phases with a slab perovskite-like structure have been identified.